P87 Is fraction of exhaled nitric oxide (FeNO) in asymptomatic older teenagers related to preschool wheeze and chronic cough?. (14th November 2013) - Marshall, LR; Beardsmore, C; Monteiro, W; Pescatore, A; Kuehni, C; Gaillard, E
Abstract : Background: Many children with preschool wheeze and chronic cough become asymptomatic in later childhood, only for asthma to be diagnosed in adulthood (1). A previous study found in individuals with apparently outgrown childhood asthma, fraction of exhaled nitric oxide (FeNO) was significantly increased (2). Whether teenagers with a history of preschool wheezing or chronic cough have elevated FeNO, and whether this differs between preschool wheeze phenotypes is unknown. Aims: We compared FeNO and induced sputum inflammatory cell counts in asymptomatic teenagers from the Leicestershire Respiratory Cohort, who had persistent 'multiple trigger' wheeze (PW), transient viral wheeze (TW), persistent cough (PC), or no respiratory symptoms (controls) during the preschool years. Methods: Thirty-six subjects (mean age: 16 years) participated: 7 with PW; 12 with TW; 7 with PC; and 10 controls. FeNO was measured using a portable electrochemical analyser (NIOX MINO ® Asthma Inflammation Monitor, Aerocrine AB, Sweden). Sputum was induced with nebulised hypertonic saline and processed according to previously published protocol (3) with an adaptation for smaller samples. Results: There was no statistically significant difference in mean logFeNO between groups ( p = 0.563) (Figure 1 ). Median% sputum eosinophils for PW and TW groups were significantly higher than in controls. Sputum total cell counts were significantly greater in PW and PC groups than in controls. Conclusions: We did not find evidence that FeNO in asymptomatic adolescents is related to history of preschool wheeze and chronic cough. However, we found evidence that eosinophilic airway inflammation is increased in asymptomatic adolescents with preschool PW and TW. The relationship between FeNO and evidence of elevated inflammatory cell counts in sputum remains enigmatic. These findings have implications for the understanding of the natural history of preschool wheeze and chronic cough. References: Roorda RJ. Prognostic factors for the outcome of childhood asthma in adolescence. Thorax 1996;51(S1):S7-S12. van Den Toorn LM, et al . Adolescents in clinical remission of atopic asthma have elevated exhaled nitric oxide levels and bronchial hyperresponsiveness. Am J Respir Crit Care Med 2000 Sep;162(3 Pt 1):953–957. Pin I, et al . Use of induced sputum cell counts to investigate airway inflammation in asthma. Thorax 1992;47:25–9.